2003
DOI: 10.1023/b:ddas.0000004522.36120.08
|View full text |Cite
|
Sign up to set email alerts
|

Non-Organ-Specific Autoantibodies in Nonalcoholic Fatty Liver Disease: Prevalence and Correlates

Abstract: Eighty-four consecutive subjects with nonalcoholic fatty liver disease (NAFLD) were tested for non-organ-specific autoantibodies (NOSA) by indirect immunoflorescence. Indices of insulin resistance and biochemical and anthropometric parameters were assessed. The overall prevalence of anti-nuclear-antibodies (ANA), smooth muscle antibodies (SMA) and anti-mitochondrial-antibodies (AMA) was 35.7% (30/84), 18 subjects (21.4%) being positive for ANA, 4 (4.7%) for SMA, 6 for ANA and SMA, and 2 for AMA. NOSA-positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
98
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(106 citation statements)
references
References 45 publications
7
98
0
1
Order By: Relevance
“…Liver biopsy evaluation is also important for a patient with a clinical suspicion of autoimmune liver disease. Up to 20% of NAFLD have positive serologies for antinuclear antibody, antismooth muscle antibody, and/or antimitochondrial antibody [36][37][38] ; therefore, liver biopsy evaluation might be the only means of determining the underlying cause of the disease. Furthermore, surgeons have shown that intraoperative visualization is commonly not correct for the prediction of either steatosis or advanced fibrosis, and thus liver biopsy is currently being recommended in the morbidly obese bariatric population at the time of surgery [39] .…”
Section: Value Of Liver Biopsy Evaluation In Nonalcoholic Fatty Livermentioning
confidence: 99%
“…Liver biopsy evaluation is also important for a patient with a clinical suspicion of autoimmune liver disease. Up to 20% of NAFLD have positive serologies for antinuclear antibody, antismooth muscle antibody, and/or antimitochondrial antibody [36][37][38] ; therefore, liver biopsy evaluation might be the only means of determining the underlying cause of the disease. Furthermore, surgeons have shown that intraoperative visualization is commonly not correct for the prediction of either steatosis or advanced fibrosis, and thus liver biopsy is currently being recommended in the morbidly obese bariatric population at the time of surgery [39] .…”
Section: Value Of Liver Biopsy Evaluation In Nonalcoholic Fatty Livermentioning
confidence: 99%
“…Elevated C-reactive protein (CRP) concentrations are related to insulin resistance, to MS, predict coronary heart disease, diabetes and have also been reported in NAFLD. 16,17 A high prevalence of nonorgan-specific autoantibodies, has been found in NAFLD associated with insulin resistance 18 and in patients with coronary atherosclerosis as well. 19 These data indicate that systemic subclinical inflammation typically associated with MS are also found in NAFLD.…”
Section: Pathogenesismentioning
confidence: 99%
“…Loria and colleagues documented that the high titers of ANA may be an indicator for a severe insulin resistance in those patients [71].…”
Section: ) Clinical Significance Of Autoimmunity In Liver Diseases Amentioning
confidence: 99%